2016
DOI: 10.1039/c6ra08191f
|View full text |Cite
|
Sign up to set email alerts
|

Extremely high external quantum efficiency of inverted organic light-emitting diodes with low operation voltage and reduced efficiency roll-off by using sulfide-based double electron injection layers

Abstract: Inverted organic light-emitting diodes (IOLEDs) have great potential application in flat-panel displays. High energy consumption, efficiency roll-off, and poor electron injection are key issues limiting the use of IOLEDs. Here, we present IOLEDs with extremely low driving voltage, high efficiency and efficiency rollup by employing double electron injection layers (D-EILs) composed of metal sulfide and cesium carbonate (Cs 2 CO 3 )-doped 4,7-diphenyl-1,10-phenanthroline (Bphen). We demonstrate that the use of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The value is higher than 36 mV dec –1 for the Pt, 31 while it is much lower than 85 mV dec –1 for pure CZTS and moreover, most of the reported values for non-noble metal HER catalysts, such as MoS 2 alone, 32 MoS 2 CFs, 33 bare CoS 2 , 34 and other nonprecious metal catalysts are listed in (Table 1) The exchange current density ( j 0 ) of the HER on I-CZTS/GO is obtained to be 908 mA cm –2 , higher than that of pure CZTS (882 mA cm –2 ) and also outperforming many reported non-noble metal HER catalysts. 35 These results indicate the high catalytic activity of I-CZTS/GO with respect to most of the nonprecious systems from the literature. The LSV polarization curves of the I-CZTS/GO composite at various scan rates are shown in Figure S5, and it can be seen that the current density increases from 133 to 164 mA cm –2 with the rising scan rate from 10 to 100 mV s –1 at a potential of −0.3 V versus the reversible hydrogen electrode (RHE), showing that the catalytic activity of I-CZTS/GO composites toward HER is fewer pretentious by scan rates, which indicates interfacial electron transfer is diffusion controlled.…”
Section: Resultsmentioning
confidence: 63%
“…The value is higher than 36 mV dec –1 for the Pt, 31 while it is much lower than 85 mV dec –1 for pure CZTS and moreover, most of the reported values for non-noble metal HER catalysts, such as MoS 2 alone, 32 MoS 2 CFs, 33 bare CoS 2 , 34 and other nonprecious metal catalysts are listed in (Table 1) The exchange current density ( j 0 ) of the HER on I-CZTS/GO is obtained to be 908 mA cm –2 , higher than that of pure CZTS (882 mA cm –2 ) and also outperforming many reported non-noble metal HER catalysts. 35 These results indicate the high catalytic activity of I-CZTS/GO with respect to most of the nonprecious systems from the literature. The LSV polarization curves of the I-CZTS/GO composite at various scan rates are shown in Figure S5, and it can be seen that the current density increases from 133 to 164 mA cm –2 with the rising scan rate from 10 to 100 mV s –1 at a potential of −0.3 V versus the reversible hydrogen electrode (RHE), showing that the catalytic activity of I-CZTS/GO composites toward HER is fewer pretentious by scan rates, which indicates interfacial electron transfer is diffusion controlled.…”
Section: Resultsmentioning
confidence: 63%
“…In this work, an inverted device structure was used to fabricate diode-pumped OSLs. We have recently found that the device structure of ITO/ZnS/Bphen/AND:DSA-ph/NPB/MoO3/Al could perform as extremely high-efficiency inverted OLEDs due to the formation of a favorable interfacial dipole layer at the metal sulfide-organic interface [ 20 ]. Furthermore, the inverted structure could also have great potential application for providing longer device lifetime because it can keep water and oxygen out from beneath sensitive electron injection materials [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the diode-pumped OSLs with POFP film acting as gain media were demonstrated. Zinc sulfide (ZnS) was applied as an electron injection layer (EIL) for its efficient electron injection [ 20 ], while the molybdenum oxide (MoO 3 ) acted as a hole injection layer (HIL). The device architectures were ITO/ZnS (2 nm)/POFP (150 nm)/AND:2wt%DSA-ph (10 nm)/NPB (10 nm)/2T-NATA (device E: 50 nm, device F: 125 nm)/MoO 3 (5 nm)/Al (100 nm).…”
Section: Methods/experimentalmentioning
confidence: 99%
“…The ZnO:CsCO 3 film was deposited on ITO by spin‐coating of 3000 rpm for 60 s followed by an annealing for 15 min at 150 °C. In previous studies, it has been shown that the use of salts, such as Cs 2 CO 3 or CsF, as a source of Cs component for electron injection and transport enhancement in organic devices . PEI films with different concentrations were spin‐coated onto ZnO at a speed of 6000 rpm for 60 s followed by an annealing for 15 min at 150 °C to obtain thicknesses of 5, 10, and 15 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Organic light‐emitting diodes (OLEDs) have been applied in display and lighting technologies for their advantages of flexibility, response time, and picture quality . Compared with the conventional structures, it has been shown that inverted structures are more stable in air because the air‐sensitive cathode in the inverted OLEDs is passivated by the other organic layers . Another advantage of inverted OLEDs relies on the deposition first of the electron transport layer (ETL) which is less soluble than hole transport layer (HTL) so that is theoretically easier to build an OLED starting from the most aggressive solvent to softer ones .…”
Section: Introductionmentioning
confidence: 99%